Ultrasound in cervical traumatic neuromas after neck dissection in thyroid carcinoma patients: descriptive analysis and diagnostic accuracy - Marcos, Vinicius Neves; Danilovic, Debora Lucia Seguro; Pereira, Fernando Linhares; Tsunemi, Miriam Harumi [UNESP]; Kulcsar, Marco Aurelio Vamondes; Hoff, Ana Oliveira; Domingues, Regina Barros; Chammas, Maria Cristina; de Freitas, Ricardo Miguel Costa (Archives of Endocrinology and Metabolism, 2023)
Objective: Cervical traumatic neuromas (CTNs) may appear after lateral neck dissection for metastatic thyroid carcinoma. If they are misdiagnosed as metastatic lymph nodes (LNs) in follow-up neck ultrasound (US), unnecessary and uncomfortable fine-needle aspiration biopsy are indicated. The present study aimed to describe US features of CTNs and to assess the US performance in distinguishing CTNs from abnormal LNs. Subjects and methods: Retrospective evaluation of neck US images of 206 consecutive patients who had lateral neck dissection as a part of thyroid cancer treatment to assess CTN´s US features. Diagnostic accuracy study to evaluate US performance in distinguishing CTNs from abnormal LNs was performed. Results: Eight-six lateral neck nodules were selected for analysis: 38 CTNs and 48 abnormal LNs. CTNs with diagnostic cytology were predominantly hypoechogenic (100% vs. 45%; P = 0.008) and had shorter diameters than inconclusive cytology CTNs: short axis (0.39 cm vs. 0.50 cm; P = 0.03) and long axis (1.64 cm vs. 2.35 cm; P = 0.021). The US features with the best accuracy to distinguish CTNs from abnormal LNs were continuity with a nervous structure, hypoechogenic internal lines, short/long axis ratio ≤ 0.42, absent Doppler vascularization, fusiform morphology, and short axis ≤ 0.48 cm. Conclusion: US is a very useful method for assessing CTNs, with good performance in distinguishing CTNs from abnormal LNs.
Keywords: neck dissection; Neuroma; thyroid neoplasms; ultrasonography